2013
DOI: 10.3758/s13414-013-0479-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of exploratory procedures by blind and sighted adults and children

Abstract: The study examined exploratory procedures (EPs) of congenitally blind and sighted children and adults on a haptic match-to-sample task. The aim was to examine the influence of age, visual status, and familiarity on the use of EPs when people haptically examine the object properties of weight, size, exact shape, and texture. EPs in the first and last of four series of trials were compared. The results showed that all four groups chose the same dominant EP for examining the four different object properties, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
4
22
0
Order By: Relevance
“…Apart from modifications associated with the environment and the material used, it is suggested that special teachers should take a number of important points into consideration when they want to include into their instructions types of haptic exploratory procedures. Those points may include: a) teaching students to use proper haptic exploratory strategies depending on the information they want to extract on each occasion (Homa et al, 2009;Lederman & Klatzky, 1987, 1992Withagen et al, 2013); b) prompting students to use both hands (Morash et al, 2014); c) prompting students to use all fingers and particularly index fingers (Morash et al, 2014); d) encouraging students to engage in training and rich tactile experiences to improve methods of manipulation (Warren, 1994); e) teaching exploratory procedures, not just using geometric shapes but also using real objects that students with visual impairment encounter in their day-to-day lives (Picard, Lebaz, Jouffrais & Monnie, 2010) and f) gaining the appropriate training and knowledge to adopt tactile exploration strategies and teach students with visual impairment how to choose the right strategy for every occasion (Douglas, McCall, McLinden & Pavey, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from modifications associated with the environment and the material used, it is suggested that special teachers should take a number of important points into consideration when they want to include into their instructions types of haptic exploratory procedures. Those points may include: a) teaching students to use proper haptic exploratory strategies depending on the information they want to extract on each occasion (Homa et al, 2009;Lederman & Klatzky, 1987, 1992Withagen et al, 2013); b) prompting students to use both hands (Morash et al, 2014); c) prompting students to use all fingers and particularly index fingers (Morash et al, 2014); d) encouraging students to engage in training and rich tactile experiences to improve methods of manipulation (Warren, 1994); e) teaching exploratory procedures, not just using geometric shapes but also using real objects that students with visual impairment encounter in their day-to-day lives (Picard, Lebaz, Jouffrais & Monnie, 2010) and f) gaining the appropriate training and knowledge to adopt tactile exploration strategies and teach students with visual impairment how to choose the right strategy for every occasion (Douglas, McCall, McLinden & Pavey, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The type of exploratory movement used depends on the information an individual wants to extract from the object (Homa, Kahol, Tripathi, Bratton & Panchanathan, 2009). Also, the information that an individual obtains through exploratory movements is associated with the object's global shape, exact shape, weight, volume, texture, material, temperature and function (Lederman & Klatzky, 1987;Withagen, Kappers, Vervloed, Knoors & Verhoeven, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently unclear whether there are systematic differences in EPs between the blind and sighted. Withagen et al (2013) found that age was a more important factor than visual status, EPs becoming more efficient in adults than children, while Rovira et al (2011) found that, for 2-D raised-line patterns, the blind were more likely to use lateral motion while the sighted needed to use contour-following. On balance, we conclude that differences in EPs are unlikely to account for the observed difference in view-dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Lederman, Klatzky, Chataway, & Summers, 1990; Theurel et al, 2012; Woods et al, 2008); and lacked distinctive textural features (cf. Newell et al, 2001; Withagen et al, 2013) that could have served as cues for changes in orientation. Lacey et al (2007) reported that, for such objects, normally sighted individuals show viewpoint-dependence in both visual and haptic object recognition.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these movement strategies could be implemented as distinct motor commands to drive artificial hands used to explore objects and materials in remote and dangerous environments. Currently, the annotation of haptic exploration episodes is done by observing video recordings of object handling and manually annotating it with the EPs [ 4 ]. This is a laborious task that involves substantial subjectivity on the part of the observer.…”
Section: Introductionmentioning
confidence: 99%